The oral contraceptive cycle and its influences on maximal and submaximal endurance parameters in elite handball players - Mathy, Astrid; Wessner, Barbara; Haider, Patricia; Tschan, Harald; Triska, Christoph (Frontiers in Physiology, 2024)
The usage of the oral contraceptive pill is widespread among athletes of various levels. However, there is limited knowledge on how the intake of the pill alters the submaximal and maximal endurance parameters between the oral contraceptive phases. Therefore, the aim of this study was to examine potential differences between the pill intake and withdrawal phase on endurance-related parameters in first-division handball players. In total, 15 female team handball players performed two graded exercise tests until volitional exhaustion on a motorized treadmill. Tests were performed during the pill intake (days 16–17) and withdrawal phase (day 2–3). Throughout the test, respiratory gases were measured breath-by-breath, and the heart rate was measured continuously. Before and after the graded exercise test, blood samples were obtained in order to assess the blood lactate concentration. Before each test, venous blood samples were taken to determine endogenous sex hormone levels. Ventilatory parameters (V˙O2, V˙CO2, and V˙E, and respiratory equivalents for V˙O2 and V˙CO2) were measured, and the oxidation of fat and carbohydrates was calculated. A paired-sample t-test was used to assess differences between the two time points, and the significance was accepted as p < 0.050. Significant differences with lower values during the consumption phase were found for absolute (mean difference ± SD: 88 ± 131 mL∙min−1; p = 0.021) and relative V˙O2peak (mean difference ± SD: 1 ± 2 mL∙min−1∙kg−1; p = 0.012). Higher values during the consumption phase were found for submaximal respiratory equivalents for V˙O2 (mean difference ± SD: −1.1 ± 1.7; p = 0.028) and V˙CO2 (mean difference ± SD: −0.9 ± 1.5; p = 0.032). No differences were found for all other parameters, including differences for endogenous sex hormones (p > 0.050). The results of the current study suggest only marginal and physiologically insignificant differences in endurance-related parameters between oral contraceptive phases.